Virtual Mass Method for Solution of Dynamic Response of Composite Cushion Packaging System. (8th October 2012) - Lu, Fu‐de; Tao, Wei‐ming; Gao, De
Abstract : A composite package cushioning system consists of multiple layers of cushioning materials in series. Such composite cushioning systems will enhance the protection capability to the packaged products. However, the dynamic analysis of the composite cushioning system becomes more difficult because of the strong nonlinear characteristics of cushioning materials. To overcome the difficulty in calculation, the method of virtual mass is proposed to form the system equations of motion as a set of multidimensional ordinary differential equations so that the Runge–Kutta method can be applied to obtain the numerical solution of the system response. The rationale of the method is shown both analytically and numerically by assessing the reliability of the virtual mass method. For a specific composite cushioning system consisting of two layers of expanded polystyrene (EPS) and expanded polyethylene (EPE) materials, experiments were carried out first for each material to obtain the stress–strain behaviours under both static and dynamic loadings. On the basis of these data, the stress–strain constitutive models were developed for EPS and EPE. Then, experiments were conducted for the composite cushioning system under different system parameters, and the measured data are compared with the analytical results using the method of virtual mass. The agreement between the analytical and the experimental results substantiates the accuracy of the proposed virtual mass method. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : A composite package cushioning system consists of multiple layers of cushioning materials in series. The method of virtual mass is proposed to form the system equations of motion as a set of multidimensional ordinary differential equations so that the Runge–Kutta method can be applied to obtain the numerical solution of the system response. The rationale of the method is shown both analytically and numerically by accessing the accuracy of the virtual mass method.